Modernitet, globalisering och medier (Sociologisk Forskning, 1998)
Modernity, globalisation and mediaConceptions of time and space lie at the heart of many prevalent discourses on modernity and globalization. These conceptions are variably based on ideas of modern media of communication having developed as part of technological and other transformations throughout the modern era. One major aim of the article is to scrutinize some of the literature that claims to establish historical links between modernity, globalization and the media. For one thing, it is asserted here that globalization is not simply a logical outcome of modernity. Depending on the chosen historical perspective, the relationship might be the contrary one - global interdependencies appearing prior to both early and late modernity. There is also a criticism of the spatialization turn in social and cultural theory. It does not capture the subtle dialectics of time and space as these dimensions are reconstituted by the media, not least on the global level. In this context and as an exposé of continuity vs. change arguments the author considers the critiques of media imperialism and postjournalism